Pragmaticaspects of digital literacy: rapport management in mobile phone communication - Cantamutto, Lucía (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
This paper is part of a larger study on mobile communication in the Spanish language variety of Buenos Aires (Argentina) and the peninsular Spanish (Spain) from a sociolinguistic and pragmatic perspective, which aims to identify discursive regularities and phenomena of pragmatic variation, and associated to contextual variables. Communication via SMSes, subscribed to “electronic style” (Vela Delfa 2005, 670), progressively has distinguished characteristics that differen-tiate it from other communications produced in digital environment. In the analysis, we consider the how, on one hand, despite the brevity required by character-limit, pragmatics elements of expressive, appellative, phatic functions of language are verified, and, second, how these issues reflect attitudes related to rapport management between speakers, therefore, questions of (im)politeness and, in addition, negotiation of image. These linguistics practices associated with digital literacy, as knowledge to be acquired, impact on social practices and attitudes derived from the adaptation to the context of interac-tion. Central features of pragmatic aspects related to (im)politeness, which were collected by test of social habits (Hernández Flores, 2002) implemented in both study communities, will be presented. The present study is framed within the Interactional Sociolinguistics’ approach, concepts from Cyberpragmatics(Yus, 2010) and sociocultural Pragmatics. We follow Spencer-Oatey (2000-2011) and Fant & Granato (2002) in the study of rapport management.